Sugarcane (Saccharum spp. hybrids) biotechnology research in South Africa - Sandra J. Snyman; Aimee C. Koch; Robyn M. Jacob; Shailesh V. Joshi; Sharon A. McFarlane; Christell van der Vyver; R. Stuart Rutherford (In Vitro Cellular & Developmental Biology - Plant, 2025)
Commercial sugarcane, Saccharum spp. hybrids, arose from interspecific crossing in the late 1890s and the resultant complex polyploid genome has challenged conventional breeding approaches. The grower- and miller-funded South African Sugarcane Research Institute (SASRI) has a 100-yr history which began by breeding for local agroclimatic regions. Biotechnology for cultivar improvement was introduced in the early 1990s. Collaborations with local research institutes and the International Consortium for Sugarcane Biotechnology (ICSB) have enabled advances such as the genome sequence being published this year, signifying a real opportunity to implement bioinformatic and marker techniques for targeted cultivar enhancement. This review focuses on biotechnology-related interventions that have supported sugarcane research and resulted in SASRI-bred N cultivars being widely grown in many sub-Saharan African sugarcane-growing countries.

Endophytic Beauveria bassiana in sugarcane and associated Eldana saccharina host plants in South Africa - Nongcebo S. Memela; R. Stuart Rutherford; Stefan Schmidt (BioControl, 2024)
Eldana saccharina Walker is a problematic sugarcane stalk borer pest in South Africa. Twenty-eight sugarcane genotypes ( Saccharum spp. hybrids) and seven different species of host plants of E. saccharina were surveyed for the presence of endophytic Beauveria bassiana sensu lato ( s.l. ). Collectively, 326 plant samples (roots, stems, or leaves) were collected from five locations in sugarcane-producing areas (KwaZulu-Natal; South Africa). Following plant surface disinfection, 128 fungal colonies morphologically resembling Beauveria spp. were isolated from internal plant tissues. The sequence analysis of the internal transcribed spacer region confirmed that 13 representative isolates were B. bassiana. s.l . Eight B. bassiana isolates were recovered from E. saccharina natural host plants, and 120 from different sugarcane stem parts (top node, top internodes, bottom node, and bottom internode). Endophytic B. bassiana isolates were recovered from 22 of 28 sugarcane genotypes surveyed. The number of B. bassiana isolates obtained from different sugarcane parts differed significantly, with more B. bassiana isolates obtained from the top than the bottom internodes. Furthermore, sugarcane genotypes N31 and N41 yielded B. bassiana from all plant parts sampled, while five sugarcane genotypes harbored no B. bassiana isolates. This study demonstrates for the first time the natural occurrence of endophytic B. bassiana strains in sugarcane plants and E. saccharina host plants in South Africa.

Methylglyoxal-induced enhancement of somatic embryogenesis and associated metabolic changes in sugarcane (Saccharum spp. hybrids) - Tendekai Mahlanza; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Agronomic evaluation and molecular characterisation of the acetolactate synthase gene in imazapyr tolerant sugarcane (Saccharum hybrid) genotypes - Motselisi J. Koetle; Dyfed Lloyd Evans; Varnika Singh; Sandy J. Snyman; R. Stuart Rutherford; M. Paula Watt (Plant Cell Reports, 2018)

Potential of Fusarium sacchari-tolerant mutants in controlling Eldana saccharina and borer-associated Fusarium stem rot in sugarcane - Tendekai Mahlanza; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (European Journal of Plant Pathology, 2015)

5-Azacytidine as a tool to induce somaclonal variants with useful traits in sugarcane (Saccharum spp.) - Ashlin Munsamy; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (Plant Biotechnology Reports, 2013)

In vitro generation of somaclonal variant plants of sugarcane for tolerance to Fusarium sacchari - Tendekai Mahlanza; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (Plant Cell Reports, 2013)

An in vitro mutagenesis protocol for the production of sugarcane tolerant to the herbicide imazapyr - Aimée C. Koch; Sumita Ramgareeb; R. Stuart Rutherford; Sandra J. Snyman; M. Paula Watt (In Vitro Cellular & Developmental Biology - Plant, 2012)